(untitled) (Al-Qamar, 2025)
Before the Prophetic era (ﷺ), not only Arab society but the entire world was engulfed in darkness. However, after the Prophet’s (ﷺ) arrival, the enlightened teachings of Islam replaced this deep darkness with light. The Prophet (ﷺ) guided the people of Arabia towards such social progress that within a few years, the region of Hejaz attained the honor of leadership for the entire world and became a source of blessings for all. This paper will include the measures taken by the Prophet (ﷺ) to achieve this transformation, such as granting dignity to women who were previously dishonored, freeing slaves, guiding businesspeople towards prosperity through charity, assisting the needy through a structured system of Bait-ul-Mal (public treasury), transforming generational enmities into bonds of brotherhood, beautifying society through moral teachings, and cleansing both outward and inward impurities by prohibiting wrongdoing. Additionally, a contemporary application of these timeless measures will be discussed to address modern-day social decline and moral degradation. The paper will explore how Prophetic measures can be applied to resolve present-day issues, such as challenges to modern family values, intellectual and practical corruptions, and deteriorating interpersonal relationships, providing a framework for their reform.